POLA PEMBINAAN KAMPUNG BINAAN KELUARGA SAKINAH DI KABUPATEN SIAK (STUDI IMPLEMENTASI PERATURAN BUPATI NOMOR 14 TAHUN 2016 DI KECAMATAN SIAK) - Aprilia Ningsih; Hasim As’ari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Family life is the core of the community development process so that every family is expected to build the household into a family which acquired the peace of life full of love and affection as the main purpose of marriage. Kampung Binaan Keluarga Sakinah (KBKS) from the Ministry of Religions RI which is then applied by the Government of Siak Regency through Kampung Binaan Keluarga Sakinah. Siak subdistrict is one of the place of performance the activities of the contruction of small-scale family Hometown Sakinah. The method of this research is use qualitative method with approach case studies. The concept of the theory is theory of Implementation Success by Grindle (Agustino:2016) i.e. the Content Of Policy: interest that affect the type of benefits, the degree of change is to be achieved, the layout of the retrieval the decision, implementing programs, and resources used. Content Of Policy: power interest and strategy, characteristics of the institution and the ruling regime, and compliance and responsiveness of the executor. Data collection done with interview, observation, and documentation. Based on the result of the analysis, conclusion is the implementation of such activities can improve practice and knowledge as well as the religion that quantitative show that public has been able and execute well and true worship. But there are still many problem in terms of implementation in causing this activity has not been running optimally, moreover on the indicator by Grindle.Keywords : Policy, Implementation, Built Village of Sakinah Family